Mid-crisis restructuring law reform in the UK - Van Zwieten, K (Springer Nature, 2023)
Economic shocks create insolvency law-making space, generating opportunities for legal reform that may be absent in good times. Policymakers may suddenly acquire a mandate to resource institutions or drive through a change in the law where in good times such reforms were likely to be foiled by interest group capture, or simply unlikely to get sufficient political traction. A crisis, then, is an opportunity for the well-prepared insolvency policymaker. Insolvency rule-making in crisis conditions is, however, plainly also risky. Making best use of the opportunity implies making more than temporary changes to the regime. But design choices made mid-crisis will almost inevitably be influenced by the features of the crisis itself, generating a risk that the result of the reform effort will be distorted law, ill-suited to the achievement of the lawmaker’s objectives in the long run. This paper considers the permanent restructuring law reforms enacted in the UK during the first wave of the Covid-19 pandemic. At first glance, these reforms appear to exemplify the case of the well-prepared policymaker, poised to drive through carefully planned changes to the law when the opportunity arises. On closer inspection, however, a different picture emerges. The permanent measures, which were enacted in a fast-track legislative process, departed from the Government’s pre-pandemic plan in material and undesirable ways. In some cases, these deviations mean that the original objective has not been achieved at all; in others, the objective has been at least partially achieved, but at unnecessary cost. Overall, the UK experience appears to better exemplify the risks of attempting insolvency law reform in a crisis, than the opportunities that a crisis affords to an insolvency policymaker.